Nauka o kamieniach i jej źródła w cyklu kazań Nuptiae Agni Antoniego Węgrzynowicza - Kroczak, Jerzy (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
This article centers on the literary achievements of preacher Antoni Węgrzynowicz (1658-1721) from the collection Nuptiae Agni . Gody Baranka apokaliptycznego… (Krak.w 1711) – „Nuptials of the Apocalyptic Lamb” (transl.) – in which there are, among other things, a series of conceptual sermons – refer to the fragment of Apocalypse 21, 19-20, relates to the twelve precious stones being the foundations of the Heavenly Jerusalem, traditionally associated with the names of the apostles. The author presents spiritual content, ingeniously built on knowledge of natural sciences regarding the properties of precious stones, derived from the writings of past and contemporary naturalists, from encyclopedic texts, biblical commentaries, baroque symbolographic compendia, and specialized literature for church speakers. The article discusses these sources of knowledge and seeks to present the writing strategies used by Węgrzynowicz concerning the study of precious stones.